Digital Capability Implementation Gaps and Their Impact on MSME Performance: A Study of Micro, Small, and Medium Enterprises in Banjarbaru, Indonesia - Surti, Surti (University Merdeka Malang, 2025)
This study investigates the impact of digital capability, digital literacy, and digital infrastructure on the performance of Micro, Small, and Medium Enterprises (MSMEs) in Banjarbaru, Indonesia. Using a quantitative approach with a sample of 387 MSMEs, the results reveal that all three variables significantly and positively influence MSME performance, with digital capability having the strongest effect (coefficient = 0.352), followed by digital literacy (0.285) and digital infrastructure (0.223). Despite high adoption rates of digital communication platforms (e.g., 99.5% for WhatsApp Business and 94.6% for social media), significant gaps were identified in digital business management aspects, such as digital bookkeeping (27.9% adoption). The model explains 64.74% of the variation in MSME performance. The study recommends five key programs—Digital Business Transformation, Digital Creative Hub, Tech Funding Access, Digital Talent Pool, and MSME Digital Market Network—to enhance the digital competitiveness of Banjarbaru’s MSMEs. These initiatives require collaboration among government, academia, and the private sector to address structural challenges and leverage digital opportunities in the region. The findings highlight the critical need for targeted interventions to bridge digital implementation gaps and optimize the adoption of digital technologies for sustainable MSME growth.